2004
DOI: 10.1038/nature02419
|View full text |Cite
|
Sign up to set email alerts
|

Variable female preferences drive complex male displays

Abstract: Complexity in male sexual displays is widely appreciated but diversity in female mate choice has received little attention. Males of many species have sexual displays composed of multiple display traits, and females are thought to use these different traits in mate choice. Models of multiple display trait evolution suggest that these traits provide females with different kinds of information in different stages of the mate choice process, or function as redundant signals to improve the accuracy of mate assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(129 citation statements)
references
References 17 publications
2
125
1
1
Order By: Relevance
“…First, females of many spe- cies often have preferences for multiple male traits (Brooks and Endler 2001a;Coleman et al 2004). Here, a single trait (g max ) explained 64% of the genetic variance in female preference functions for nine male traits.…”
Section: Discussionmentioning
confidence: 99%
“…First, females of many spe- cies often have preferences for multiple male traits (Brooks and Endler 2001a;Coleman et al 2004). Here, a single trait (g max ) explained 64% of the genetic variance in female preference functions for nine male traits.…”
Section: Discussionmentioning
confidence: 99%
“…Decades of research exploring the effect of female preference has established that this mode of selection can lead to exaggerated traits [1][2][3][4]. Despite this, we still have a relatively poor understanding of if/how female preferences have shaped the more extreme examples of sexual ornamentation seen in the animal kingdom, specifically those characterized by an elaboration of a whole suite of signals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Okida et al (2010) showed a significant e#ect of vocalisation during the display on the mating success in this species. Recent studies on the bower display showed that various characteristics of display a#ected the male mating success, including the quality of the bower structure (Borgia 1985b), decorations (Borgia 1985b, Madden 2003a, 2003b), male's painting behaviour , vocal mimicry (Lo#redo & Borgia 1986, Coleman et al 2007, and intensity of behavioural display (Patricelli et al 2002, Coleman et al 2004. Thus, the bower display is composed of multiple sexual signals.…”
Section: Multiple Components Of Displaymentioning
confidence: 99%
“…Thus, the bower display is composed of multiple sexual signals. However, whether individual signals have di#erent functions or convey the same message as redundant signals is still under debate (Coleman et al 2004, Bravery & Goldizen 2007.…”
Section: Multiple Components Of Displaymentioning
confidence: 99%